The blood-pressure raising secretion of the ischaemic kidney - Fasciolo, Juan Carlos (1938)
The co-existence of arterial hypertension and renal lesions has been observed for a long time. This fact has induced many investigators to attempt the production of arterial hypertension by experimental modification of the kidney. The methods used have been numerous and varied, e.g. surgical removal of part of the kidney, ligature of the renal artery or some of its branches, reduction of the calibre of the renal vein, ligature of the ureter, multiple emboli of the kidney, irradiation of the kidney, toxic nephritis, renal compression, etc. References to the principal experiments of this nature can be found in the articles by Braun-Menendez [1932], Goldblatt [1937] and Fasciolo [1938b].